2007
DOI: 10.1103/physrevb.75.174508
|View full text |Cite
|
Sign up to set email alerts
|

Weak anharmonic effects inMgB2: A comparative inelastic x-ray scattering and Raman study

Abstract: We study anharmonic effects in MgB2 by comparing Inelastic X-ray and Raman scattering together with ab-initio calculations. Using high statistics and high q resolution measurements we show that the E2g mode linewidth is independent of temperature along ΓA. We show, contrary to previous claims, that the Raman-peak energy decreases as a function of increasing temperature, a behaviour inconsistent with all the anharmonic ab-initio calculations of the E2g mode at Γ available in literature. These findings and the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 48 publications
(174 reference statements)
5
51
0
Order By: Relevance
“…Early work indicated that superconductivity in MgB 2 [389] originated with a strong EPI caused by anharmonic E 2g phonons. Later this interpretation has been called into question, and it has been argued that MgB 2 is not particularly anharmonic [390]. Furthermore, the adiabatic approximation itself has been questioned because the electrons may not respond instantly to nuclear displacements [390].…”
Section: The Adiabatic Epi In Superconductorsmentioning
confidence: 99%
“…Early work indicated that superconductivity in MgB 2 [389] originated with a strong EPI caused by anharmonic E 2g phonons. Later this interpretation has been called into question, and it has been argued that MgB 2 is not particularly anharmonic [390]. Furthermore, the adiabatic approximation itself has been questioned because the electrons may not respond instantly to nuclear displacements [390].…”
Section: The Adiabatic Epi In Superconductorsmentioning
confidence: 99%
“…26 This is consistent with the later harmonic phonon dispersion results 27,28 obtained from inelastic x-ray scattering. 27,29,30 As for the MgB 2 synthesized at the different temperatures, there are a number of defects both in and between the crystals. Eisterer et al have researched the influence of disorder on the superconducting properties of MgB 2 wires and extracted the mean free path of the charge carriers in the band from the Goŕkov-Goodman relation.…”
Section: Methodsmentioning
confidence: 99%
“…However, despite the tremendous progress achieved in understanding of superconductivity in MgB 2 , many of its fundamental properties related to phonons and electron-phonon (e − ph) coupling are still puzzling and remain under intense debate. Thus such important issues as, e.g., the reduced isotope effect, 2,3,4 the nature of the strong broad continuum in Raman spectra, the unusually broad linewidth of the E 2g phonon mode seen in Raman spectra, 5,6,7 the inconsistency between the results of Raman scattering and x-ray measurements, 8,9,10 and the role of non-adiabatic effects 8,11,12,13,14 have not yet found satisfactory explanations.As for the electronic part of the e−ph picture of superconductivity in MgB 2 , it has received substantially less attention than the phonon part. In particular, in all evaluations of the e−ph interaction the adiabatic approximation has been used, and even in ab initio calculations 15 of T c the dynamical Coulomb interaction has been considered in its static form.…”
mentioning
confidence: 99%
“…4 we show the calculated dispersion of the bare σπ mode along with the bare E 2g phonon mode 37 compared to the experimental data. 8,13 One can see how the two bare curves cross each other close to the Γ point. Due to its localization in the boron plane the σπ plasmon strongly interacts with the boron E 2g phonon mode resulting in strong hybridization of these boson modes.…”
mentioning
confidence: 99%
See 1 more Smart Citation